PENGARUH KOMBINASI EKSTRAK ETANOL KULIT PUTIH BUAH SEMANGKA (CITRULLUS LANATUS (THUNB.)) DAN AIR BONGGOL PISANG KEPOK (MUSA ACUMINATA X MUSA BALBISIANA (ABB GROUP)) TERHADAP PERTUMBUHAN RAMBUT TIKUS PUTIH JANTAN - M. Ikhwan Setiawan; Anna P. Roswiem; Ika Wahyu Pertiwi (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
White skin of watermelon and the liquid of kepok banana tree trunk empirically widely used as hair growth, In addition ethanol extract white skin of watermelon and the liquid of kepok banana tree trunk has also been scientifically proven able to accelerate the growth hair of the rat. However the research activity of the combination of the two against the hair growth has never done. The purpose of this research is to know the combination of both these extracts which can give of the most activity is good for hair growth. Ethanol extract of white skin of watermelon extraction is done by of maceration using a solvent of ethanol 70 %, as for getting the test sample is liquid of kepok banana tree trunk done by cutting down banana tree trunk approximately 50 cm above the ground surface then the stem of banana leaf his satin-the core then covered with plastic and silenced for one night. The results showed that the combination of liquid of kepok banana tree trunk and Ethanol extract white skin of watermelon (2:1) have a long hair growth activity higher than the positive control (Minoxidil), While hair growth activity of weights lower than the positive control (Minoxidil)